Analisis Kelayakan Usaha Produksi Batik Tulis di Desa Ngentrong Kecamatan Karangan Kabupaten Trenggalek - Oktavia Ananda Zulfa; Kunto Inggit Gunawan (Pusat Riset dan Inovasi Nasional, 2024)
The research has a purpose to be achieved to determine and analyze the feasibility of the written batik production business in the batik industry center located in Ngentrong Village, Karangan District, Trenggalek Regency financially. The research was conducted through a qualitative descriptive method involving 6 informants. Based on the analysis conducted, the highest B/C Ratio value reached 0.60>1, while the lowest value of 0.19>1 indicate that the business is feasible. The R/C Ratio results also show that the hand-written batik production business meets the criteria for feasibility with the highest value of 1.60>1 and the lowest value of 1.19>1. The results of the analysis using ROI produce an ROI value> 0%, namely the highest value of 65.42% and the lowest value of 8.70%, so the hand-written batik production business is feasible to run. Analysis using BEP produces the highest BEP unit value of 258 units and the lowest BEP unit value of 131 units. Analysis using BEP rupiah results in the highest value of Rp96,728,322.00 and the lowest BEP rupiah value of Rp46,017,367.00. Based on the analysis that has been conducted in this study, it can be concluded that the written batik production business at the batik industry center in Ngentrong Village, Karangan District, Trenggalek Regency is feasible.